Transcriptional Regulation of the Outer Membrane Porin Gene ompW Reveals its Physiological Role during the Transition from the Aerobic to the Anaerobic Lifestyle of Escherichia coli - Xiao, Minfeng; Lai, Yong; Sun, Jian; Chen, Guanhua; Yan, Aixin (Frontiers in Microbiology, 2016)
Understanding bacterial physiology relies on elucidating the regulatory mechanisms and cellular functions of those differentially expressed genes in response to environmental changes. A widespread Gram-negative bacterial outer membrane protein OmpW has been implicated in the adaptation to stresses in various species. It is recently found to be present in the regulon of the global anaerobic transcription factor FNR and ArcA in E. coli. However, little is known about the physiological implications of this regulatory disposition. In this study, we demonstrate that transcription of ompW is indeed mediated by a series of global regulators involved in the anaerobiosis of E. coli. We show that FNR can both activate and repress the expression of ompW through its direct binding to two distinctive sites, -81.5 and -126.5 bp respectively, on ompW promoter. ArcA also participates in repression of ompW under anaerobic condition, but in an FNR dependent manner. Additionally, ompW is also subject to the regulation by CRP and NarL which senses the availability and types of carbon sources and respiration electron acceptors in the environment respectively, implying a role of OmpW in the carbon and energy metabolism of E. coli during its anaerobic adaptation. Molecular docking reveals that OmpW can bind fumarate, an alternative electron acceptor in anaerobic respiration, with sufficient affinity. Moreover, supplement of fumarate or succinate which belongs to the C4-dicarboxylates family of metabolite, to E. coli culture rescues OmpW-mediated colicin S4 killing. Taken together, we propose that OmpW is involved in anaerobic carbon and energy metabolism to mediate the transition from aerobic to anaerobic lifestyle in E. coli.